Unjuk Kerja Jaringan Seluler 2G dan 3G PT. XL Axiata di Area Jawa Tengah Bagian Utara setelah Proyek Swap dan Modernisasi - Eva Yovita Dwi Utami; Pravita Ananingtyas Hanika (Universitas Syiah Kuala, 2015)
The increasing number of customers and the need for reliable communication require the availability of coverage, sufficient capacity and good quality of mobile communications networks. New BTS implementation is required to cover a wider area with good network quality. However, it often requires high cost and long time to get permission from the government and local residents. Swap and Modernization Project is a project that swap the previous 3G equipment using BTS 3900 Huawei with Ericsson RBS 6000 and modernize the 2G RBS 2000 to RBS 6000 and then carry out parameter settings to optimize the network. In this paper, we report the results of mobile network performance after Swap and Modernization projects had been done in terms of the signal strength improvements, which are showed by Rx Level, RSCP and CDD Dump parameters. The study was conducted in PT XL Axiata Northern Areas of Central Java with D5 cluster as a sample. The results show improvement of Rx Level that increased by 89.93 %, and RSCP value increased by 58.36 %. The swap and modernization of the BTS and parameter settings are able to improve CDD Dump parameters. These improvements are able to expand the coverage area of cluster D5 sites.